Narrative review: Personalized art learning with AI - A new frontier in education - Yahaya, Sumiyah; Zalay @ Zali, Abdul Aziz (Journal of Islamic, Social, Economics and Development, 2025)
This narrative review examines how artificial intelligence (AI) is transforming personalized learning in art education, synthesizing emerging trends, challenges, and implications for pedagogy, equity, and creativity. AI introduces innovative tools that enable adaptive and individualized learning experiences, offering opportunities to enhance student engagement and support creative co-production. However, concerns remain regarding originality, equitable access, and the authenticity of artistic expression. A purposive literature search was conducted across Scopus, Web of Science, ERIC, and Google Scholar, covering 2013–2024, including both peer-reviewed and grey literature relevant to AI applications in creative education and personalized learning. Key themes include AI-driven adaptive instructional systems, creative collaboration, and ethical debates surrounding authorship and creativity. Significant gaps persist in long-term empirical research, inclusive design, and educator preparedness. This review provides a foundational synthesis of AI-enabled personalized art learning and proposes a forward-looking research agenda that balances innovation with critical reflection and educational equity.